Learning the fundamentals of building performance simulation through an experiential teaching approach. Issue 3 (4th May 2019) - Beausoleil-Morrison, Ian
Abstract : It is relatively easy to train architects and engineers to operate BPS tools and to produce results, but there is considerable evidence to show that it is quite difficult to produce accurate results, even for experienced users. I believe that BPS suffers from a credibility gap and that its full potential will only be realized once we adequately prepare users to effectively apply tools with full knowledge of their applicability, modelling limitations, and default methods and data, and provide them the skill set to scrutinize their results. An experiential approach for teaching the fundamentals of BPS through a learning spiral composed of four modes of learning has been devised. The approach and the learning outcomes that have been achieved through each of the learning modes are demonstrated in this article through examples extracted from the teaching of a semester-long post-graduate course.